The role of SMEs in the transition to a circular food system - Rovira Antonell, Meritxell (2022)
The main aim of this master’s thesis is to study the role of small and medium-sized enterprises (SMEs) in the transition to a circular economy. In particular, the aim is to understand the views of SMEs operating in the Finnish food system, the views of Finnish experts in the circular economy, and also how SMEs can practically better adopt circular economy practices. In order to do this, ten interviews have been carried out to understand the views of managers of six Finnish SMEs in the food system, as well as four Finnish experts in the circular economy. The results show that SMEs, especially those with the circular economy embedded at the core of the business, can play a significant role in the circular transition as disruptors.